2015
DOI: 10.29313/mimbar.v31i2.1491
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pengembangan Kemandirian Pelaku Muda Agribisnis “ Brain Gain Actors” di Jawa Barat

Abstract: Brain gain is one approach innovation to the regeneration of agriculture and ruraldevelopment actors who are a warm discourse in the world. Independence developmentof agribusiness young actors (AYA) are educated and skilled representation of brain gainprocess. As a complex process, brain gain needs to be initiated and developed into aregeneration policy in Indonesia. Quality management business perspective asserts, toarrive at a policy, it is necessary strategies. This study aims to formulate a independencedev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
5
0
4
Order By: Relevance
“…Several previous studies have shown that there are several determining factors for farmers to do agribusiness, including personal characteristics [30,31,32] There are studies on entrepreneurship in organic agriculture [23], growth trends and increasing entrepreneurial activities in agriculture and related activities [24,8]. There are several studies that focus on farming management and supporting farming for entrepreneurship [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown that there are several determining factors for farmers to do agribusiness, including personal characteristics [30,31,32] There are studies on entrepreneurship in organic agriculture [23], growth trends and increasing entrepreneurial activities in agriculture and related activities [24,8]. There are several studies that focus on farming management and supporting farming for entrepreneurship [19].…”
Section: Introductionmentioning
confidence: 99%
“…Conditions in the red chili cluster in handling post-harvest red chillies are still experiencing problems. Productivity to maintain the continuity of supply of red chili in addition to the technical aspects of cultivation that refers to standard operating procedures (SOP), can also be increased by taking into account the human resources they have, the level of independence of young agribusiness actors (PMA) which is relatively weak, especially in terms of quality and power competitiveness, as well as suggesting several collaborative strategies (Setiawan et al, 2015). Not only vegetables are affected by climate change but fruit producers in various countries often experience various risks associated with climate change and weather (Tsyr-Shuay, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Itis something that encourages the entrepreneurial soul of people in the countrysides. If there is a stagnation of this application, the entrepreneurial innovation will not develop (stagnant) (Setiawan, et al, 2015).…”
Section: Innovation Trialabilitymentioning
confidence: 99%